Cholesterol, Blood Glucose and Hemoglobin Profiles of Urban Adolescents - Setyorini, Yuyun; Darmawan, Rendi Editya; Ardesa, Yopi Harwinanda; Rinawati, RR Sri Arini Winarti; Astuti, Rini Wuri (Poltekkes Kemenkes Surakarta, 2023)
Background: Prevention of heart and cardiovascular disease must be carried out as early as possible with routine biochemical examinations. Aim of this study is to describe the profile of Cholesterol, Blood Glucose and Hemogobin in urban adolescents. Methods: This research method uses a descriptive design with a cross sectional approach. The sample population in this study was 63 nursing students at the Surakarta Health Polytechnic. The study was conducted in August 2023 and the sample was selected randomly. Data were analyzed descriptively. Results: The average cholesterol level was 197mg/dl, the average blood sugar level was 91.1 mg/dl and the average hemoglobin was 13.2 g/dl. Conclusion: The incidence of hypercholesterolemia was high in respondents. This condition is possible due to insufficient consumption of vegetables and lack of physical activity resulting in high cholesterol levels. These specific findings can help create policies to develop more strategic evidence-based interventions, through grouping risk factors in controlling the risk of non-communicable diseases in adolescents.